2023
DOI: 10.1039/d2fo02463b
|View full text |Cite
|
Sign up to set email alerts
|

Orally administered octacosanol improves liver insulin resistance in high-fat diet-fed mice through the reconstruction of the gut microbiota structure and inhibition of the TLR4/NF-κB inflammatory pathway

Abstract: 1-Octacosanol (Octa) is reported to possess many physiological properties. However, its relative mechanism has not been illustrated yet. Herein, we aimed to investigate the effect of Octa on insulin resistance...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 70 publications
(84 reference statements)
1
3
0
Order By: Relevance
“…The involvement of Bacteriodetes in insulin resistance and their interaction with GLP-1 secretion has also been suggested by Hwang et al, who reported an improvement in insulin resistance linked to the lower presence of Bacteroidetes and Firmicutes associated with GLP-1 secretion [34]. Our data also therefore link GLP-1-stimulated secretion in the ileum with insulin resistance and microbiota restructuration in these animals, though the effect is contrary to that described by other authors [33].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The involvement of Bacteriodetes in insulin resistance and their interaction with GLP-1 secretion has also been suggested by Hwang et al, who reported an improvement in insulin resistance linked to the lower presence of Bacteroidetes and Firmicutes associated with GLP-1 secretion [34]. Our data also therefore link GLP-1-stimulated secretion in the ileum with insulin resistance and microbiota restructuration in these animals, though the effect is contrary to that described by other authors [33].…”
Section: Discussionsupporting
confidence: 77%
“…GLP-1 receptor in the ileum showed a positive correlation with NEFA, which is also strongly linked to insulin resistance [32]. Ileum GLP-1 and GLP-1R parameters showed a positive correlation with Bacteriodetes and Verrucomicrobiota, respectively, though an increase of both phyla has been associated with an improvement in insulin resistance [33]. The involvement of Bacteriodetes in insulin resistance and their interaction with GLP-1 secretion has also been suggested by Hwang et al, who reported an improvement in insulin resistance linked to the lower presence of Bacteroidetes and Firmicutes associated with GLP-1 secretion [34].…”
Section: Discussionmentioning
confidence: 94%
“…These compounds activate nuclear factor erythroid 2-related factor 2 (Nrf2) signaling, henceforth modulating immune response [ 41 ]. Likewise, studies have reported that ergosta family of compounds cause attenuation of mitogen-activated protein kinase/activator protein-1 (MAPK/AP-1) pathway and interleukin-6/Janus kinase/signal transducer and activator of transcription (IL-6/JAK/STAT) pathway which results in modulation of immune cum inflammatory pathways [ 39 , 42 , 43 ]. In addition to this JAKs are cytoplasmic tyrosine kinases that could phosphorylate and dimerize the STATs, these dimerized entities are translocated to nucleus and bind with DNA which causes selective expression of genes responsible for immune activation.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, Tadashi Takeuchi and others found that individuals with a high content of Chaetomium in the human intestine often have higher insulin resistance and higher fecal monosaccharide content; however, individuals with more Bacteroides have lower insulin resistance and lower monosaccharide content in feces [71]. Nevertheless, Yin-Yi Ding and others have proved through experiments that insulin resistance can be prevented by reducing the content of Firmicutes and increasing the content of Bacteroides and wart microflora [72]. These results indicate that increasing the number of intestinal-associated flora and reducing proinflammatory signal transduction can effectively intervene in insulin resistance.…”
Section: Interactions Between Alcohol and Intestinal Floramentioning
confidence: 99%